2021
DOI: 10.1177/0036850420983625
|View full text |Cite
|
Sign up to set email alerts
|

Experiment investigation of injection parameters effects on injection stability of a high pressure common rail system

Abstract: High pressure common rail system can precisely control the injection time and injection pressure to improve the thermal efficiency of the engine. The injection characteristics of the system can affect the combustion and emission process of the engine. Injection stability is defined as variation characteristics of injection. This could have an unignored influence on combustion and engine output, while few study has been published. The primary objective is to establish evaluation systems and methods for injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In contrast to the traditional diesel engine fuel injection system, high-pressure common rail injection systems are widely used in various diesel engines because of their capacity for the flexible adjustment of injection pressure, independent and flexible control of injection timing and quantity, and high control accuracy, and they can effectively improve the economic aspects, power, and emissions of diesel engines [6][7][8][9][10]. In high-pressure common rail systems for diesel engines, the common rail pipe [11,12], as an important energy storage element in the common rail system, has an important impact on the control of the rail pressure fluctuations, common rail pressure and fuel injection quantity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the traditional diesel engine fuel injection system, high-pressure common rail injection systems are widely used in various diesel engines because of their capacity for the flexible adjustment of injection pressure, independent and flexible control of injection timing and quantity, and high control accuracy, and they can effectively improve the economic aspects, power, and emissions of diesel engines [6][7][8][9][10]. In high-pressure common rail systems for diesel engines, the common rail pipe [11,12], as an important energy storage element in the common rail system, has an important impact on the control of the rail pressure fluctuations, common rail pressure and fuel injection quantity.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time in the future, they will still be an important source of power for construction machinery, ships, military equipment, and other fields 1 . As the “brain” and “heart” of a high‐speed and high‐power diesel engine, the high‐pressure common rail injection system enables a precise adjustment of the fuel injection to increase the output power of a diesel engine, improve fuel economy, and reduce the emission of nitrogen oxides and particulate matter significantly 2–4 . As the core component of a high‐pressure common rail injection system, a fuel injector represents the highest technology level and development difficulty for the common rail system, and it exerts an important impact on the power performance, fuel economy, and emission control of diesel engines 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…1 As the "brain" and "heart" of a high-speed and high-power diesel engine, the high-pressure common rail injection system enables a precise adjustment of the fuel injection to increase the output power of a diesel engine, improve fuel economy, and reduce the emission of nitrogen oxides and particulate matter significantly. [2][3][4] As the core component of a high-pressure common rail injection system, a fuel injector represents the highest technology level and development difficulty for the common rail system, and it exerts an important impact on the power performance, fuel economy, and emission control of diesel engines. 5,6 The strong flow recirculation and local depression inside a fuel injector provide favorable conditions for the occurrence of cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al 27 observed IP and IT's effect with split injection technology on all measurable characteristics of a CRDI single-cylinder diesel engine. Gao et al 28 observed the impact on the injection stability parameters of the CRDI system like injection speed, mass of injection, delay, and injection rate.…”
Section: Introductionmentioning
confidence: 99%